2000
DOI: 10.1161/01.cir.101.15.1854
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Endothelium-Dependent Regulation of Ventricular Relaxation in Pressure-Overload Cardiac Hypertrophy

Abstract: Background-Endothelium-derived nitric oxide (NO) selectively enhances myocardial relaxation and may benefit diastolic function. Left ventricular hypertrophy (LVH) is characterized by abnormal myocardial relaxation and endothelial dysfunction. We investigated endothelium-dependent regulation of LV relaxation in moderate pressureoverload LVH induced by aortic banding in guinea pigs. Methods and Results-Isolated ejecting hearts of banded or sham-operated animals (shams) were studied. The specific agonists for end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 51 publications
3
42
0
2
Order By: Relevance
“…Previous reports have suggested that the relaxant effect of NO is impaired in hypertrophied myocardium. 26) Our model of cardiac hypertrophy by volume-overload was accompanied by diastolic dysfunction even in the chronic inhibition of NO synthesis. In this volume-overload model, we reported that diastolic dysfunction was associated with the reduced gene expression of Ca 2+ cycling proteins.…”
Section: Discussionmentioning
confidence: 91%
“…Previous reports have suggested that the relaxant effect of NO is impaired in hypertrophied myocardium. 26) Our model of cardiac hypertrophy by volume-overload was accompanied by diastolic dysfunction even in the chronic inhibition of NO synthesis. In this volume-overload model, we reported that diastolic dysfunction was associated with the reduced gene expression of Ca 2+ cycling proteins.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, in general, endothelium-mediated (drug-and shear stress-stimulated) dilation of isolated coronary arteries is reduced in hypertensive humans 11,[53][54][55][56][57] and animals, 19,21,32,36,45,51,52,[58][59][60][61][62] while the endothelium-independent vasodilatory responses to sodium nitroprusside and adenosine are often unaltered. 21,32,45,55,63 There are exceptions to these general observations 18,33,50,[63][64][65][66] and the vessel type (conduit vs resistance artery), 45,57 the mode of precontraction, 33 and the vasodilator protocol 45,56,61,67 or eliminated 58,68,69 by inhibitors of eNOS in isolated coronary vessels from hypertensive animals, suggesting that NO remains an important component of vascular function even when its bioavailability is reduced in hypertension.…”
Section: Nitric Oxide-mediated Vasomotor Function Of Isolated Coronarmentioning
confidence: 99%
“…9,10 In the pressure overload model by aortic banding, the impaired LV relaxation was improved effectively by antioxidant treatment, such as vitamin C or deferoxamine, indicating that excess ROS can induce LV abnormal relaxation. 11,12 To reduce ROS for cardioprotection, potassium-rich diet may be one of the candidates, because physiological increase of potassium concentration inhibited ROS formation from endothelium or white blood cells. 13 Furthermore, the cardiac hypertrophy was improved by potassium supplementation in deoxycorticosterone acetate/Na mice independent of blood pressure (BP).…”
mentioning
confidence: 99%